Cohabitation among Older Adults - Suzanna Smith (EDIS)
“Most of the time when we think about cohabiting couples, we imagine younger adults who are living together before they get married, or instead of marrying. But, according to the 2000 census, there are more than a million individuals over the age of 50 who are cohabiting, and this number is increasing as baby boomers reach their 50s and 60s.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, March 2012.